Micropropagation and elicited production of triterpenoid saponin glycosides and stigmasterol via precursor and elicitor feeding in Bacopa floribunda (R.Br.) Wettst.—A potential nootropic herb - Otari, Shreedhar S.; Devkar, Suraj P.; Patel, Suraj B.; Ghane, Savaliram G. (Frontiers in Plant Science, 2023)
Bacopa floribunda (Family: Plantaginaceae) is used in folklore medicines for the management of cognitive dysfunction. It has nootropic, anti-aging, anti-inflammatory, anti-cholinesterase, and antioxidant properties. We developed an efficient and reproducible protocol for in vitro propagation of B. floribunda using the nodal explants. We assessed the effects of Murashige and Skoog (MS) medium fortified with various PGRs, precursors and elicitors and their optimal combinations on regeneration and production of total saponins, triterpenoid saponin glycosides (bacoside A3, bacopaside X, bacopaside II and bacosaponin C) and stigmasterol content in in vitro grown biomass of B. floribunda. The growth of the shoots and roots was stimulated by MS + 2.0 mg/l BAP + 2.0 mg/l KIN and MS + 0.5 mg/l IAA + 0.5 mg/l IBA + 1.0 mg/l NAA, respectively. After 10 weeks of acclimatization, plantlets of B. floribunda had a survival rate of 95%. Highest total saponin content (35.95 ± 0.022 mg DE/g DW) was noted in the treatment of MS + 2.0 mg/l BAP + 1.5 μM SQ. Similarly, total triterpenoid saponin glycosides and stigmasterol were found maximum in biomass derived from MS + 2.0 mg/l BAP + 1.5 μM SQ and MS + 2.0 mg/l BAP, respectively. At the same treatments, bacoside A3 (1.01 ± 0.195 mg/g DW), bacopaside II (43.62 ± 0.657 mg/g DW), bacopaside X (1.23 ± 0.570 mg/g DW), bacosaponin C (0.19 ± 0.195 mg/g DW) and stigmasterol (7.69 ± 0.102 mg/g DW) were reported. Present findings will help to highlight B. floribunda as a potent memory enhancing herb, as well as in future also it could be a potential substitute to B. monnieri. The current work is the first to describe the micropropagation and the elicited production of bioactive metabolites from the in vitro grown biomass of B. floribunda. In addition, further research is needed on production of bioactives, their pharmacological effects, and the elicited production using callus, cell suspension, and hairy root cultures.